Ratlarda Gebeliğin Farklı Periyotlarında İnce Bağırsaklarda Mast Hücrelerinin Dağılımı - Uslu, Sema; Tatar, Musa (Sivas Cumhuriyet University, 2022)
The gastrointestinal tract has different characteristics. The gastrointestinal tract is affected by the enlarging uterus as pregnancy progresses. The enlargement of the uterus changes the digestive organs, especially the metabolism of the stomach and intestines. Anatomical changes produce acute abdominal changes. In addition to the mechanical effects caused by the growing uterus, high progesterone levels cause delayed gastric emptying and increased gastrointestinal transit time. Stomach and intestinal motility are also affected, resulting in lower transit times. Mast cells are cells that are activated and show degranulation under all kinds of stress conditions. These cells are considered to be cells that play an important role in the physiological and pathological responses of the immune system by showing both proinflammatory and immunosuppressive functions. Maternal malnutrition adversely induces fetal bowel development and function through the maternal intestinal barrier, intestinal content, structure, and peripheral circulation. In this study, samples were taken from the small intestine in 3 different trimesters of pregnancy. Tissue samples taken from duodenum, jejunum and ileum were fixed in Carnoy solution for 12 hours. Paraffin blocks were prepared after tissue follow-up without washing. Paraffin blocks were formed from the samples and 5-6 µ thick sections were taken and stained with 0.5% Toluidine Blue to determine the distribution of mast cell number. After staining, the distribution of mast cells in the lamina propria + submucosa and tunica serosa layers was examined. It was determined that mast cells changed numerically in the duodenum, jejunum and ileum in the small intestine according to the layers and according to the gestational periods. It is thought that this study will contribute to the literature on this subject.

Gastrointestinal sistem farklı özelliklere sahiptir. Gastrointestinal sistem gebelik ilerledikçe genişleyen uterustan etkilenir. Uterusun genişlemesi sindirim organlarını, özellikle mide ve bağırsakların metabolizmasını değiştirir. Anatomik değişiklikler, akut abdominal değişiklikler oluşturur. Büyüyen uterusun neden olduğu mekanik etkilerin yanı sıra, yüksek progesteron seviyeleri, gecikmiş mide boşalmasına ve gastrointestinal geçiş süresinin artmasına sebep olur. Mide ve bağırsak motilitesi de etkilenir, daha düşük geçiş sürelerine neden olur. Mast hücreleri her türlü stres koşulunda aktive olan ve degranülasyon gösteren hücrelerdir. Bu hücreler hem proinflamatuar hem de immunsupresif fonksiyonlar göstererek bağışıklık sisteminin fizyolojik ve patolojik yanıtlarında önemli rol oynayan hücreler olarak kabul edilmektedirler. Annenin yetersiz beslenmesi, bağırsak içeriği, yapısı ve periferik dolaşım vastasıyla, annenin bağırsak bariyeri ile fötal bağırsak gelişimini ve işlevini olumsuz yönde indükler. Yapılan bu çalışmada gebelikte 3 farklı trimesterde ince bağırsak kısımlarından örnekler alındı. Duodenum, jejunum, ileumdan alınan doku örnekleri Carnoy solusyonunda 12 saat tespit edildi. Yıkama yapılmaksızın doku takibi sonrası parafin bloklar hazırlandı. Örneklerden parafin bloklar oluşturuldu ve 5-6  kalınlığında kesitler alınıp mast hücre sayısının dağılımını belirlemek için %0.5’lik Toluidine Blue ile boyandı. Boyama sonrasında lamina propriya+submukoza ve tunika seroza katmanlarında mast hücrelerinin dağılımları incelendi. İnce bağırsakta duedenum, jejunum ve ileumda katmanlara göre ve gebelik dönemlerine göre mast hücrelerinin sayısal olarak değiştiği tespit edildi. Yapılan bu çalışmanın bu konudaki literatüre katkı sağlayacağı düşünülmektedir.
Keywords: Veterinary Surgery; Mast hücresi; İnce bağırsak; Veteriner Cerrahi; Rat; Pregnancy; Mast cell; Small intestine; Rat; Gebelik; Mast hücresi; İnce bağırsak; Rat; Gebelik